Domain Decomposition Methods in Science and Engineering XXII - Dickopf, Thomas; Gander, Martin J.; Halpern, Laurence; Krause, Rolf; Pavarino, Luca F. (Springer, 2016)
Preface -- Part I: Plenary Presentations -- Part II: Minisymposia -- Part III: Contributed Presentations.